PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUKMENINGKATKAN HASIL BELAJAR MATEMATIKASISWAKELAS IVA SD NEGERI 75 PETANI - Nur Asiyah; Hamizi Hamizi; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Problems in this study is the result of low-grade elementary school mathematics learning IVA 75 Petani with an average value of 67.50. This research aims to improve learning outcomes Mathematics Elementary School fourth grade students 75 Petani Cooperative Learning Model Application STAD. Design research is action research (PTK) with 2 cycles. Based on research data anlisis , the average percentage of the activity of teachers in the first cycle of the first meeting rose 50% to 62.5 %% in the second meeting. The first meeting of the second cycle of 70.83%, increased again at the second meeting of the second cycle to 83.33%. The percentage of student activity at the first meeting of the first cycle of 45.8% increased to 66, %% in the second meeting. The percentage of student activity At the first meeting of the second cycle of 70.8% increased to 83.3% in the second meeting of the second cycle. Student learning outcomes in basic score with an average value of 67.50 and the second cycle increased with an average value of 75.42 class with 11.73% increase in the percentage of learning outcomes and the percentage of students who reached 62.50% KKM, and the second cycle increased again by an average of 85.41 with the percentage improvement class learning outcomes 26.53% and the percentage of students who achieve 80% KKM. These results indicate that the application of cooperative learning model type STAD can improve learning outcomes Mathematics Elementary School fourth grade students 75 PetaniKey Words : Learning Model STAD, Mathematics Learning Outcomes